Guinea - The Livestock Rehabilitation Project - World Bank (Washington, DC, 2012)
The Livestock Sector Rehabilitation Project, operational from 1986 through 1995, was seen as essential in facilitating the new government's implementation of its economic strategy when it came to office in 1984. Previous government policy had required that 10 percent of all herds be sold at a fixed price through the State Cattle Marketing Agency, encobe. This caused many herders to emigrate and hide their animals in forests or outside the country. In addition, poor animal health represented a severe constraint to agricultural productivity and growth on which approximately 30 percent of the country's rural population (160,000 families) depended. All the livestock sector reforms took place within the context of a major overhaul of the National Livestock Directorate.